Extracting and Investigating the Success Factors of Digital Transformation in Textile and Garment Enterprises: Based on the TOE Framework (Journal of Fiber Bioengineering and Informatics, 2024)
This paper extracts 13 success factors based on the TOE framework in the three dimensions of Technology,Organization, and Environment (TOE). The factors are developed from investigating the challenges in thedigital transformation of textile and garment enterprises and based on the literature and case studies onthe success factors of digital transformation within the TOE theoretical framework. Descriptive statisticsand factor analysis are performed on ample data from 201 textile and garment enterprises to verify theapplicability of the TOE framework for the classification of success factors of digital transformation oftextile and garment enterprises. The basic situation of the digital application of textile and garmententerprises is then summarised. The study finds that the organisational factors have the highest scores,followed by technical factors. From the observation indicators of 13 detailed success factors, the averagescore is greater than 4, indicating that the role of these success factors in textile and garment enterprisesis generally recognised. The “digital strategic thinking” of senior managers has the highest score, followedby the “digital transformation project team.” Environmental factor scores of enterprises in the BeijingTianjin Hebei region are the highest, followed by enterprises in the Yangtze River Delta and Pearl RiverDelta regions. Medium and large enterprises have higher scores for technical factors and organisationalfactors. Finally, the paper discusses which success factors should be addressed and improved.
Keywords: Digital Transformation; Success Factors; TOE Framework; Textile; Garment Enterprises